EXPLORING QUANTUM COMPUTING ALGORITHMS: POTENTIAL IMPACT ON CRYPTOGRAPHY AND OPTIMIZATION (International Journal of Food and Nutritional Sciences, 2021)
This paper examines the transformative potential of quantum computing algorithms in two critical domains: cryptography and optimization. We analyze how quantum algorithms, particularly Shor's and Grover's algorithms, could revolutionize current cryptographic systems and optimization problems. The research explores both the theoretical foundations and practical implications of these quantum algorithms, highlighting potential vulnerabilities in existing systems and opportunities for enhanced computational capabilities.